Diagnóstico de los establecimientos comerciales que disponen de propaganda y publicidad exterior para la creación de un anteproyecto de ordenanza en la ciudad de Puyo - Lara Ledesma, Tania Guadalupe (2015)
Improper use of propaganda and outdoor advertising by commercial establishments, and the lack of an ordinance to regulate and control this kind of activities in Puyo, produces different types of impacts on the social level and risk for bad location of billboards. As such in this research work, a “Diagnosis of commercial establishments with outdoor advertising propaganda for the creation of a draft ordinance in the city of Puyo” was performed. So it is based on the objective of proposing a mechanism for controlling commercial advertising and outdoor advertising to the Decentralized Government of Canton Pastaza has developed an ordinance that aims to contribute to the prevention and control of environmental pollution in Puyo. We applied as one of the instruments of data collection the survey, also to secondary bibliographical sources as the national and international legal regime that protects the environment, the environmental management performed by the Municipality of Pastaza, among others. Resulting in an inherent need to raise the proposed ordinance to regulate and punish environmental violations, to set formally and materially an ordinance for the administrative prosecution of environmental damage that causes a bad advertising publicity to support the reduction of environmental pollution, which threatens the constitutional right of people to live in a healthy and ecologically balanced environment